AN ANALYSIS OF STUDENTS PERCEPTION ON THE USE OF E-READER APPLICATION IN LEARNING READING: A Descriptive Qualitative Study at SMAN 16 Gowa - Sunarti; Syam, Ummi Khaerati; Ardiana (Journal of Computer Interaction in Education, 2021)
This research aimed to find out the effect of E-book Reader application on students’ reading comprehension at the second grade of SMAN 16 Gowa. The researcher applied descriptive qualitative research design. The subject of this research was 25 students. The result of this research showed that there were five positive effects by used E-book Reader application were E-book Reader application makes the students read more effectively, E-book Reader application makes easier for students to identify reading structures and main idea, E-book Reader application make students easier to read by using the features available, E-book Reader application makes students enthusiastic in reading and the last by using E-book Reader application the students save time and place. Type the abstract here (10pt). Abstract, which comprised of approximately 250 words, provides a brief description of problems, aims, the method used, and results. It emphasizes research results in which written in single line spacing with left and right margin are 0.5 cm narrower than the main text. 4 to 5 keywords must be written to describe the research scope observed, as well as the main terms undergirding the research. These keywords can be single and/or combined words